Ruled singular minimal surfaces - Aydin, Muhittin Evren; Kara, Ayla Erdur (Elsevier, 2024)
In this paper we study surfaces with minimal potential energy under gravitational forces, called singular minimal surfaces. We prove that a ruled singular minimal surface in a Euclidean 3-space is cylindrical, in particular as an alpha-catenary cylinder by a result of Lopez [Ann. Glob. Anal. Geom. 53 (4) (2018) 521-541]. This result is also extended in Lorentz-Minkowski 3-space.(c) 2023 Elsevier B.V. All rights reserved.
Keywords: alpha-Catenary; Singular minimal surface; Ruled surface; Lorentz-Minkowski space